INTEGRASI AYAT-AYAT PEDULI LINGKUNGAN DALAM PEMBELAJARAN TEMATIK TERPADU - Leny Marinda (Al'Adalah, 2019)
Integrated thematic learning in SD/MI is a learning model developed in the 2013 curriculum design. In integrated thematic learning, several subjects are integrated and delivered within one particular theme by mapping (Basic Competency) adjusted subjects. Integrated thematic learning could be delivered with various approaches and learning strategies. The purpose of thematic learning is to bring meaningful learning. Al-Baqarah verse 30 and Ar-Ruum verse 31, which talk about the use and conservation of the environment by people, in a straight line with the mapping of (Core Competence), (Basic Competence) in the theme of grade IV SD/MI. This same mandate then could allow for the integration of the interpretation of the two verses with the theme 3 subject class IV SD/MI about "Caring About Living Things". The integration between the material and the verses can be used as a reinforcement and a divine foundation in delivering material to achieve a learning object.